Biomechanical Analysis of the Canine Tuberculum Dentale - Ionut Ichim; Michael Swain; Jules Kieser (Dental Anthropology Association, 2005)
We evaluate the structural significance of the development of a canine tuberculum dentale by means of three-dimensional finite element analysis. Using a scanned human permanent canine, we construct a computer generated canine, together with alveolar bone and periodontal ligament onto which we morph two cingulum shapes, namely a flat palatal surface and a stylised tuberculum dentale. We then subject the three shapes (flat, normal cingulum, and pronounced tuberculum dentale) to a normal occlusal force and we record principal and von Mises stresses in the crowns. Our results show that stresses are concentrated at the cingulum and in the approximal areas, and that these do not differ between the three forms. We conclude that the development of a tuberculum dentale does not confer biomechanical advantage to the human canine.